Nurse’s role for Nursing Care Regnant Women Regarding Hyperemesis Gravidarum - Klankhajhon, Sirikanok; Puraya, Amaraporn; Kumpeera, Kittisak; Boonpracom, Roongtiva (NU Journal of Nursing and Health Sciences, 2020)
Hyperemesis gravidarum is a crucial issue in pregnant women. It impacts as nutrition problems during pregnancy, dehydration, and electrolyte imbalance. It also impacts on offspring outcomes as intrauterine growth retardation, premature contraction, and preterm birth including mental health problems: stress, anxiety, and fear. Lack of nutrition. The common etiology and risk factors are complications during pregnancy for example, molar pregnancy, twin pregnancy, and polyhydramnios including mental health problems: stress and anxiety. Nurse is a key significant person for assessment, tracking for etiology and risk factors and maternal and offspring consequences based on the nursing process: assessment for history, physical examination, abdominal palpation, laboratory test, and clinical diagnosis. Holistic nursing care should be planned that considers the physical, emotional, social, and spiritual needs based on the context and socioeconomic of pregnant women and their families.